2014
DOI: 10.4103/0378-6323.136896
|View full text |Cite
|
Sign up to set email alerts
|

Trichosporon inkin and Trichosporon mucoides as unusual causes of white piedra of scalp hair

Abstract: White piedra of scalp hair is considered a rare entity. We report three cases of this disorder all of whom presented with nodules on the hair. Potassium hydroxide preparations of the hair revealed clustered arthrospores and mature, easily detachable nodules. Cultures grew Trichosporon inkin in 2 patients and Trichosporon mucoides in one patient. Both these fungi are unusual causes of white piedra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…A case of white piedra of scalp due to T. inkin was earlier reported from our centre . Literature search revealed that two cases of white piedra and a case of fungal rhinosinusitis due to T. inkin have been reported from India . Isolation of this species from blood has never been reported before.…”
Section: Discussionmentioning
confidence: 95%
“…A case of white piedra of scalp due to T. inkin was earlier reported from our centre . Literature search revealed that two cases of white piedra and a case of fungal rhinosinusitis due to T. inkin have been reported from India . Isolation of this species from blood has never been reported before.…”
Section: Discussionmentioning
confidence: 95%
“…Other series indicate that the main agent of WP of the head is T. ovoides and that T. inkin predominates in inguinal and scrotal hair [2, 4, 6, 27]. However, in recent reports it is mentioned that in most of the cases identified by molecular biology or proteomics, the predominant species is T. inkin [1, 7, 10, 19, 21, 27-31]. In our series, T. inkin was isolated in 78% of the cases and to a lesser extent T. cutaneum and T. ovoides .…”
Section: Discussionmentioning
confidence: 99%
“…The most distinctive feature of this mycosis is the production of white‐brown nodules adhered to the hair shaft that may easily be detached, in contrast with black piedra nodules . Despite awareness of white piedra in the medical field since the 19th century , there is little knowledge about its mechanisms of infection in humans . Furthermore, it may occur more frequently than current estimates report, especially in tropical countries where it is believed that underdiagnosis occurs .…”
Section: Introductionmentioning
confidence: 99%